OYO Rooms: Their Hospitality and Customer Satisfaction - Shobha Sharma; Nidhi Nidhi; Smita Pathak; Rudresh Pandey; Wang Tianen; Daisy Kee Mui Hung; Huang XiaoLin; Wang Ying Xuan; Virat Rana; Prudhvi Naresh; Ranjith P.V (AIBPM Publisher, 2020)
The study is being done on the problems faced by the hospitality and tourism industries. Their growth and development. But here the research is done specifically in respect to OYO. The objective here is to tell the growth story of OYO room in the most objective way possible as a